Analysis Of Innovation Attributes Towards Adoption Interest Of Syariah Bank E-Channel Facilities - Euis Widiati; Budi Suharjo; Diah Krisnatuti (IAIN Syekh Nurjati Cirebon, 2020)
The growth of sharia banking in Indonesia which is considered slow. This study aims to analyse communication and attributes of innovation as well as the level of awareness, interest and desire of consumers in adopting e-channel of sharia banks. The data were obtained from 150 respondents selected by convenience sampling with the criteria of customers who have savings accounts both in conventional and sharia banks, and who have one of the e-channel facilities in conventional bank. The data were analysed using PLS. This study is a type of quantitative research. Respondents were taken from the entire population of conventional and sharia bank customers in Jabodetabek (Greater Jakarta). The data were obtained by face-to-face interviews using questionnaire tools. The results suggested that respondents are generally aware of the existence of e-channel facilities of sharia banks. Respondents' interest in e-channel is influenced by the strengthening of awareness regarding the benefits offered. The respondents' high interest continues to the next stage, which is the interest in using e-channels.